Investigation of the effect of particle size on froth stability - Chidzanira, Tadiwanashe (Department of Chemical Engineering, 2016)
The flotation process has been used for more than a century to separate valuable minerals from bulk ores. The separation process is based on utilising the differences in the physico-chemical properties of liberated particles, mainly the particle hydrophobicity which allows the particles to be attached to air bubbles rising from the pulp phase into the froth phase and subsequently collected to the launder. The stability of the froth phase which is be defined as the ability of bubbles to resist coalescing and bursting (Triffet & Cilliers, 2004), has been shown to have a significant effect on the efficiency of the flotation process. An unstable froth will result in poor valuable mineral recovery as these desired hydrophobic particles are detached from air bubbles and drain with the water back into the pulp phase due to bubble coalescence. On the other hand, a very stable froth may result in poor concentrate grade as the unwanted gangue materials are unselectively entrained to the concentrate. As a result, a substantial amount of research has been performed on improving control of froth stability by the manipulation of frother type and dosage. A recent study investigated the manipulation of flotation operating parameters such as air rate, froth height and depressant dosage which resulted in minimal changes in froth stability. The present study then investigated the effect of particle size and solids concentration on the stability of the froth phase using a UG2 ore and an Itabirite ore. Froth stability was determined using Bikerman tests on a laboratory scale non-continuous stability column. A novel continuously operated agitated hybrid cell was also used to assess froth stability, with water recovery and froth recovery used as proxies for froth stability. The agitated hybrid cell was then included in the experimental design as it allowed for continuous floatation system to be evaluated which resembles more industrial operations as compared to the stability column. The hybrid also incorporated the agitation zone benefits of a lab scale batch flotation cell which allows for better attachment of coarse particles and also allowing for the formation of deeper froths enabling improved froth stability measurements. The viability of using the top froth average bubble size and the side of froth axial bubble coalescence rate as froth stability proxies was also evaluated as the columns were clear glass.